2016
DOI: 10.1371/journal.pone.0165593
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Mesoscale Variability in Biofilm Shear Behavior

Abstract: Formation of bacterial colonies as biofilm on the surface/interface of various objects has the potential to impact not only human health and disease but also energy and environmental considerations. Biofilms can be regarded as soft materials, and comprehension of their shear response to external forces is a key element to the fundamental understanding. A mesoscale model has been presented in this article based on digitization of a biofilm microstructure. Its response under externally applied shear load is anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Another complexity arises from the fact that extracellular polymers of biofilms are a mixture of multiple polymers; which could interact amongst themselves. In addition, shear forces play an implicit role in shaping the structure of biofilms, the constituent polymeric molecules in the matrix can stretch, reorienting the cells thereby causing local ordering 85,86 . Beyond a certain limit of shear forces, the structures can rupture forming clusters and the clusters can hydro-dynamically interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Another complexity arises from the fact that extracellular polymers of biofilms are a mixture of multiple polymers; which could interact amongst themselves. In addition, shear forces play an implicit role in shaping the structure of biofilms, the constituent polymeric molecules in the matrix can stretch, reorienting the cells thereby causing local ordering 85,86 . Beyond a certain limit of shear forces, the structures can rupture forming clusters and the clusters can hydro-dynamically interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Both modelling [66,67] and experimental studies [57,68] have revealed the important roles that, for example, shear-stress-induced detachment of cells or increased oxygen transport to a biofilm in turbulent flow conditions play on the structure and growth of an established biofilm. From an engineering perspective, this does give some inkling of ways of managing the flow of the water distribution system to control the sloughing of biofilm material into the bulk water that ultimately emerges at the tap.…”
Section: Discussionmentioning
confidence: 99%
“…The broad reason for initial resistance to crack growth likely shares its physical origin to polymeric composite materials which results in overall similar behavior between LTF and STF behavior [18][19][20] . However, lack of clear trends in STF may indicate that these streamers may have much higher heterogeneity in their structure leading to more flaws which precipitate the fracture early in their life.…”
Section: Discussionmentioning
confidence: 99%